2017
DOI: 10.1007/s11440-017-0523-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects on geophysical–geotechnical relationships and their implications for electrical resistivity tomography monitoring of slopes

Abstract: Current assessments of slope stability rely on point sensors, the results of which are often difficult to interpret, have relatively high costs and do not provide large-area coverage. A new system is under development, based on integrated geophysical-geotechnical sensors to monitor groundwater conditions via electrical resistivity tomography. So that this system can provide end users with reliable information, it is essential that the relationships between resistivity, shear strength, suction and water content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…It provides a very fast, cheap, and efficient survey technique to characterize landslide-prone slopes (Pasierb et al, 2019). Electrical resistivity is sensitive to changes in the pore fluid resistivity and fluid saturation as the mode of current flow in the subsurface is through electrolytic conduction in the pore fluid (Hen-Jones et al, 2017). ERT is used to differentiate between soil types of differing resistivities as a result of presence of clay minerals (Shevnin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a very fast, cheap, and efficient survey technique to characterize landslide-prone slopes (Pasierb et al, 2019). Electrical resistivity is sensitive to changes in the pore fluid resistivity and fluid saturation as the mode of current flow in the subsurface is through electrolytic conduction in the pore fluid (Hen-Jones et al, 2017). ERT is used to differentiate between soil types of differing resistivities as a result of presence of clay minerals (Shevnin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ERT is used to differentiate between soil types of differing resistivities as a result of presence of clay minerals (Shevnin et al, 2007). High proportion of clay minerals has a significant influence on electrical resistivity due to surface conduction of electrical ions on the clay mineral that leads to a reduction in electrical resistivity measurement (Yamakawa et al, 2012;Hen-Jones et al, 2017). Recent studies on landslides have shown that ERT is suitable to monitor soil water content variations induced by rainfalls among other methods such as seismic refraction, seismic reflection, and self-potential and ground penetrating radar (Baroň and Supper, 2013;Boyle et al, 2018;Hojat et al, 2019;Whiteley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The complexities of establishing such relationships in practice are identified by Hen‐Jones et al (), who identified that such geotechnically coupled relationships often display hysteretic behavior in relation to seasonal variations, adding a temporal heterogeneity to the already present spatial heterogeneity present in landslide settings. An additional consideration is that, in a similar way that geophysical responses can be caused by a multitude of factors, geotechnical property variations can have a variety of causes, for example, the reduction of shear strength in soils due to loss of suction in wetting and drying cycles, and soil fabric deterioration across successive seasonal cycles (Hen‐Jones et al, ).…”
Section: Geophysical Monitoring Of Landslides: Methods and Case Studiesmentioning
confidence: 99%
“…Materials with larger void spaces, such as sands and gravels, will have smaller capillary zones (the area of saturation above the water table caused by soil suction) than cohesive materials with smaller void spaces such as clays and silts (Craig, ). In some slopes, soil suctions may be the main restraining force preventing failure (Hen‐Jones et al, ). In these settings, understanding of subsurface moisture dynamics relating to increased infiltration is critical for predicting future slope failures.…”
Section: Landslide Geophysics: An Overviewmentioning
confidence: 99%
“…This may impact the water saturation of the subsurface, and hence the electrical conductivity (e.g. Hen‐Jones et al, ; Mojica et al, ). As a result the resistivity contrast between the natural soil and archaeological remnants changes throughout the seasons of the year (Fry, ).…”
Section: Methodsmentioning
confidence: 99%